DISCOURSE ANALYSIS OF “SINDBAD AND THE PIRATES’ PIT” - Muhammad Ari Saputra (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
This Study sets out the author's view of discourse analysis and illustrates the approach with an analysis of discursive “Sindbad and the Pirates’ Pit” movies discourse in contemporary Britain, specifically in higher education. It includes a condensed theoretical account of critical discourse analysis, a framework for analysing discursive events, and a discussion of discursive practices, as well as analysis of samples of the discourse of higher education. The paper concludes with a discussion of the value of critical discourse analysis as a method in social scientific research, and as a resource for social struggle.